Personal characteristics, institutional integration and learning in Juliaca university students - Apaza Justo, Juan José (2021)
This research involves a scientific treatment and analysis between personal characteristics, institutional integration and learning in university students of the Andina Néstor Cáceres Velásquez University and Alas Peruanas University of Juliaca. It was developed within the quantitative approach, based on the correlational design -descriptive and cross-sectional. The sample included 244 students from both study houses. The instruments Ego Identity Process, Academic Self-Efficacy Scale and Institutional Integration Scale allowed verifying that there is a relationship between the variables. It was concluded that there is a high positive relationship between personal characteristics, institutional integration and student learning. Furthermore, there is a high positive relationship between the characteristic identity status, institutional integration and learning. With these evidences, the critical points that generate deficiencies in institutional integration will be measured and actions will be taken.